Pengaruh Faktor-Faktor Kinerja Keuangan, Size, Leverage, dan Pendapatan Asli Daerah Terhadap Pertumbuhan Ekonomi Dengan Alokasi Belanja Modal Sebagai Variabel Moderating Pada Kabupaten/ Kota di Provinsi Sumatera Utara - Junita Putri Rajana Harahap; Murni Daulay; Zainul Bahri Torong (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2018)
This research aimed to identify and analyze the effect of the independence ratio, effectiveness ratio , efficiency ratio , size , leverage , and the local revenue (PAD) simultaneously and partial on economic growth in the regencies and cities in North Sumatra and also to identify and analyze capital expenditures variable as moderator variable which could moderated the relationship between independence ratio, effectiveness ratio, efficiency ratio, size, leverage, and PAD in the regencies and cities in North Sumatra. This research was classified as descriptive quantitative and the objects of this research were all regencies and cities in the province of North Sumatra. The data used was a secondary data obtained from the report of the regencies and cities’ APBD in North Sumatra2011-2-15 By using a quantitative approach and the data were analyzed by using multiple linear regression analysis. The result showed independence ratio, effectiveness ratio, efficiency ratio, size, leverage, and PAD had significant effect on economic growth simultaneously. Partially, independence ratio, effectiveness ratio, efficiency ratio, size, and PAD had positive and significant effect on economic growth while leverage had no significant effect on economic growth of regencies and cities in north Sumatra. Moderator variable was able to moderate independence ratio, effectiveness ratio, efficiency ratio, size, leverage, PAD on economic growth in all regencies and cities in North Sumatra.